Deacclimation and reacclimation processes in winter wheat: novel perspectives from time-series transcriptome analysis - Vaitkevičiūtė, Gabija; Aleliūnas, Andrius; Brazauskas, Gintaras; Armonienė, Rita (Frontiers in Plant Science, 2024)
Winter wheat achieves freezing tolerance (FT) through cold acclimation (CA) – a process which is induced by low positive temperatures in autumn. The increasing occurrences of temperature fluctuations in winter lead to deacclimation (DEA), causing premature loss of FT, and the cultivars capable of reacclimation (REA) are more likely to survive the subsequent cold spells. The genetic mechanisms of DEA and REA remain poorly understood, necessitating further research to bolster climate resilience in winter wheat. Here, we selected two winter wheat genotypes with contrasting levels of FT and conducted a ten-week-long experiment imitating low-temperature fluctuations after CA under controlled conditions. Crown and leaf tissue samples for RNA-sequencing were collected at CA, DEA, and REA time-points. It is the first transcriptomic study covering both short- and long-term responses to DEA and REA in winter wheat. The study provides novel knowledge regarding CA, DEA, and REA and discusses the gene expression patterns conferring FT under temperature fluctuations. The freezing-tolerant genotype “Lakaja DS” showed elevated photosynthetic activity in leaf tissue and upregulated cryoprotective protein-encoding genes in crowns after CA when compared to the freezing-susceptible “KWS Ferrum”. “Lakaja DS” also expressed cold acclimation-associated transcripts at a significantly higher level after 1 week of DEA. Following REA, “Lakaja DS” continued to upregulate dehydrin-related genes in crowns and exhibited significantly higher expression of chitinase transcripts in leaves, when compared to “KWS Ferrum”. The findings of this study shed light on the genetic mechanisms governing DEA and REA in winter wheat, thus addressing the gaps in knowledge regarding FT under low-temperature fluctuations. The identified genes should be further examined as potential molecular markers for breeding strategies focused on developing freezing-tolerant winter-type crops. Publicly available datasets generated in this study are valuable resources for further research into DEA and REA, contributing towards the enhancement of winter wheat under global climate change.